Experimental Study on the Structural Behavior of Cast in-situ Hollow Core Concrete Slabs - Akhtar Gul; Khan Shahzada; Bashir Alam; Yasir Irfan Badrashi; Sajjad Wali Khan; Fayaz A. Khan; Abid Ali; Zahid Ur Rehman (Civil Engineering Journal, 2020)
An experimental work has been carried out to study the flexural behavior of cast in-situ hollow core reinforced concrete (HCRC) slabs constructed by using easy, cost effective and implementable techniques in field. The precast elements made of different easily available affordable material i.e. concrete, polyvinyl chloride (PVC) and plaster of paris having voided cross- sections of circular, rectangular and triangular shapes were incorporated in one direction during pouring of concrete with minimum flexural reinforcement to construct HCRC slabs. A total of 14 slab specimens including 02 specimens per specification were tested with third point loading for the assessment of flexural behavior as per ASTM standards C78/C78M. The flexural behavior of HCRC slabs with polyvinyl and plaster of paris elements having hollow cross-sections was comparable with the control solid slabs, however, HCRC slab with concrete pipes showed 7 to 8 percent reduction in flexural strength with 19 to 20 percent reduction in self-weight. All the tested specimens performed well in shear as no shear failure was observed. This study reveals that HCRC slabs with locally available material having hollow cross section elements can be used for the construction of cast in-situ monolithic construction of one-way slabs with ordinary construction techniques. Doi: 10.28991/cej-2020-03091597 Full Text: PDF